THERMODYNAMICS OF WATER SOLUBILITY AND PARTITIONING - Keppler H.; Bolfan-Casanova N. (My University, 2006)
When it was realized that nominally anhydrous minerals could be a major storage site of water in the mantle (Smyth 1987; Bell and Rossman 1992), it also became rather obvious that many mantle samples probably have lost most of their water during ascent (e.g., Ingrin and Skogby 2000). While analyses of natural samples therefore in many circumstances only provide a lower limit of the actual water content in the mantle, measurements of water solubility give an upper limit of the amount of water that might be stored in a mineral. Experimental measurements of water solubility have therefore naturally evolved in the last decades as a major tool for understanding the water storage capacity of the mantle.